Indonesia's Flooding Issues - Muliaty (Journal of Indonesian Scholars for Social Research, 2021)
Flooding is a significant and complex issue in most regions of Indonesia. Every time the rainy season comes, towns and regions throughout Indonesia are inundated by floodwaters. This qualitative research study is conducted at a library—techniques for collecting secondary data, such as journals, conferences, books, periodicals, and news. The data was analyzed by reducing, presenting, and making conclusions. The findings revealed that the floods were caused by more than just heavy rain. However, human actions such as dumping trash into rivers or cutting down trees, causing forests to be deforested, contribute to floods. Rubbish dumped into the river accumulates over time, and when it rains, the river water overflows because the flow is impeded by a massive mound of garbage, resulting in floods.